Konfigurasi Politik dan Pembentukan Hukum Islam di Indonesia: Analisis Politik Hukum terhadap Legislasi Nasional - Muhibbussabry; Nurasiah, Nurasiah; Ananda, Faisar (JOM, 2025)
This study analyzes the relationship between political configuration and law formation as a political product, as well as its implications for the development of Islamic law in Indonesia’s national legal system. Departing from the view that law is autonomous and neutral, this study proposes a political reading of law that positions Islamic law in a structural relationship with state power. Using a qualitative juridical-normative approach and political-legal analysis, this study examines how power structures, political orientations of the regime, and legislative dynamics influence the character and substance of institutionalized law. The findings show that changes in political configuration, whether democratic, authoritarian, or religiously ideological, correlate directly with the level of accommodation and restriction of Sharia norms in national law. The main contribution of this research lies in asserting that the institutionalization of Islamic law in Indonesia is not solely determined by religious normative legitimacy, but rather by political configurations that operate through legislative mechanisms and legal institutionalization. A normative comparison with the practices of other Muslim countries reveals a general pattern of political-legal relations in Islam, highlighting political-legal analysis as an essential theoretical framework for understanding the direction and future of Islamic law in Indonesia.